Migration – Germany’s past and present. Thoughts and figures - Eltges, Markus; Strubelt, Wendelin (European Spatial Research and Policy, 2019)
In this article, the history of emigration from Germany and the immigration to Germany especially in relation to its changing borders in the 20th century is discussed. After 1945 Germany was confronted with the integration of a million German refugees. Starting in the 1950s, Germany intentionally attracted foreign workers, and integrated them fairly well. The article analyses the current discussions in Germany in relation to the impact of massive immigration of refugees from non-European areas around 2015. It concludes with a position that in the time of globalisation migration needs a society-focussed and political learning process which has not yet ended and will require more learning. But countries with a declining population are well advised to see immigration as an opportunity for future growth and social diversity.